Cloud data integrity verification scheme for associated tags. Issue 95 (August 2020) - Tian, Junfeng; Jing, Xuan
Abstract: In typical cloud storage systems such as storage systems for electronic health records (EHRs), users must regularly update sensitive files that are stored in the cloud. Leakage of the operation logs (OLs) will cause severe damage to users. Therefore, it is critical to develop secure auditing techniques for verifying users OLs. Under this scenario, we propose a novel auditing scheme that realizes secure detection for users OLs. In this design, the OLs are grouped according to the types of operations, the verification tags (VTs) of the OLs are calculated by associating an operation relationship, and the cloud data integrity verification is realized by randomly detecting the correctness of VTs. We introduce a homomorphic hash function into the integrity verification of the OLs, and the verification result for the sensitive information is derived from the verification result for the public information, thereby realizing stronger privacy protection. Furthermore, our scheme also achieves efficient handling of data dynamics. The security analysis and experimental verification indicate that our scheme is secure and efficient.